(untitled) (African Journal of Biomedical Research, 2022)
Cancer affects all manner of persons irrespective of culture, socioeconomic status or background and usually takes a grave psychological toll on patients. In Ghana, the minimal level of awareness of this disease coupled with late presentation, inaccurate diagnosis and sometimes delayed initiation of treatment stirs up anxiety and depression in patients receiving antineoplastic therapy. Such anxiety and depression if not adequately managed can negatively affect patients’ response to treatment. This report proposes the path-goal theory, the situational theory and the behavioural theory as the three most ideal styles of leadership theories required in the management of patients undergoing therapy for cancer. The report also outlines steps for a systematic and comprehensive way of assessment as well as the management of cancer in Ghana.